CAMISEA GAS ANALYSIS AND NEW PERSPECTIVES - Gil-Benitez, Wilver (1999)
New alternative use of one of the most important gas resources in the history of Peru are presented. Provides information on the location of the deposit, chemical composition, historical background of natural resources, a review of the technological changes in the petrochemical and obsoletismo . Exploitation of the Camisea gas under the scenario of conventional technology leading to fuel use and potential of a second scenario with modern and emerging technology which gives a higher added value and solving economic problems of the trade balance is analyzed and once the type of pollution and ecological.